Socio-economical impacts on environment:An architects’ perspective - Nathani, Twinkle (Recent Research in Science and Technology, 2014)
It has been observed that India is gradually becoming a country of significant industrial development. Factories have grown on the landscape like weeds. Trees have been felled, fields have been up-ended, and the rivers have been progressively blackened. The sky has been choked with smoke and ash, and the people too, spend their days coughing and itching, their eyes turned forever towards the ground. Villages grow into towns, towns into cities and people have begun to live on the earth rather than within it. Pollution control, environmental doom, eco-friendly developments have never been implemented in spite of the omnipresence of the words “pollution” and “socio-economics”. How societies progress, stagnate, or regress because of their local or regional or global economy is generally analysed by socio-economics. The pattern of consumption, the distribution of incomes and wealth, the way in which people behave, and the overall quality of life is affected by socio-economics.The introduction of contaminants into the natural environment that causes adverse change has been defined as pollution. The form of chemical substances or energy, such as noise, heat or light can be taken as pollution. It has been a stupefying revelation that 4% of particulate emissions, water pollution incidents, noise and soil pollution are mainly because of the constructional works going on around the globe.Increasing energy-efficient design, construction, and building performance throughout our communities are key elements of the value proposition offered by architects. So, given the current conditions, the unique opportunity to re-create their buildings as active solutions to combating poor air quality and climate change resides in every architect’s bag. This research aims to develop guidelines for the architects to do so.